已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^2]-(cosA^3/sinA)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 04:24:16
已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^2]-(cosA^3/sinA)已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^
已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^2]-(cosA^3/sinA)
已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^2]-(cosA^3/sinA)
已知(1+tanA)/(1-tanA)=3+2倍根号2,求[(sinA+cosA)^2]-(cosA^3/sinA)
(1+tanA/(1-tanA)=3+2根号2.
1+tanA=3+2根号2-(3+2根号2)tanA
(4+2根号2)tanA=2+2根号2
tanA=根号2/2
[(sinA+cosA)^2-1]/(cotA-sinAcosA)
=(1+2sinAcosA-1)/(cotA-sinAcosA)
=2sinAcosA/(cosA/sinA-sinAcosA)
=2sinA/(1/sinA-sinA)
=2(sinA)^2/[1-(sinA)^2]
=2(sinA)^2/(cosA)^2
=2(tanA)^2
=2*1/2
=1
tanA=1+根号2/2+根号2
已知1/tana+tana=2求sina+cosa
已知1/tana+tana=2求sinacosa
化简tana+1/tana
已知tana/(tana-1)=-1 为什么tana=1/2
已知3π/4小于a小于π,tana+1/tana=-10/3,求tana,
已知tana=2,求tan2a-tana/1+tan2a·tana的值
1+tanA/1-tanA=3+2.828 tanA=
(2tana/2)/[1+(tana/2)^2]为什么=tana
1+tana/1-tana=-3
tan2a=2tana/[1-(tana)^2
求证tanA-1/tanA=-(2/tan2A)
已知cosa=1/5,tana
已知sina=1/5,且tana
已知tana=2,求1/sinacosa
已知sin2a=1,求tana
已知:secA-tanA=1,求sinA
求证(1+tanA-secA)/(1-tanA+secA)=(secA+tanA-1)/(secA+tanA+1)
证明:(tanA-secA+1)/(secA-tanA+1)=(tanA+secA-1)/(tanA+secA+1)